Perancangan Tas Khusus untuk Penggemar K-POP saat Mengunjungi Konser K-POP - Regina Nursyafitri; M Arif Waskito (Aliansi Desainer Produk Industri Indonesia (ADPII), 2022)
A social group that has the same hobbies or interests can be an opportunity to become a target for finding solutions in that group. The design of this bag is intended to suit the needs of the community when attending concerts, namely the age range of 16-33 years old. This research is motivated by the needs/opportunities of the needs of Kpop fans when attending concerts with several regulations that regulate luggage to the size of the bag used. When go to a K-pop concert, there is an item that is characteristic that makes this bag different from other bags, that item is called a lightstick. The basis of this design is also due to seeing how much they take care of this item and other considerations of luggage due to the limited bag size set by the concert organizer. The purpose of this research is to produce a bag design that is a community solution when attending concerts with a special compartment to store lightsticks so that they are safe and can still store other products. The resulting design has a novelty value that is offered, namely the development of designs from existing products besides the advantages of this designed bag having a cheaper price compared to existing products because the product is made abroad, with a compact design with reference to casual - korean look. The design process is carried out through a double diamond design thinking approach, namely by searching for data about the target user by fostering a sense of empathy, finding solutions for what products are needed, then looking for appropriate ideas, and at the end of the process a design is produced in the form of a dynamic mock-up that more or less have the size and function in accordance with the resulting design.